PENGGUNAAN MULTIMEDIA DALAM MODEL PENGAJARAN LANGSUNG UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR ILMU GIZI OLAHRAGA MAHASISWA D2-PGSD PENJAS - Faridha Nurhayati, ; Endang Sri Wahjuni, (Ordik, 2010)
One of the main problem in learning of sport nutrition study at student of sport education departement, specially D2-PGSD Penjas is lack of their motivation in following learning. This condition cause the result of learning of student less. This matter is visible from result evaluate the UAS (final exam semester) obtained average value of student still below the mark that is less than 60, even in one class nothing get the value A.             Target of this research is description of usage multimedia in direct instruction model to increase motivation and result of learning sport nutrition of D2-PGSD Penjas student.  This Research represent the class action research consisted of some cycle. Every cycle consisted of 4 phase, that is: (1) planning, (2) activity, (3) observation, (4) reflection. Amount of cycle depend on attainment of efficacy indicator every cycle, that is at least 75% student have the motivation learn high and 75% student can get the value ≥75 from test given by cycle. This Subject Research is student of D2- PGSD Penjas FIK Unesa amount to 54 people. Result of research indicate that after 2 study cycle is amount of student which motivation to learn the high 44 people (81,5%) and which motivation to learn very high counted 6 people (11,1%). While student which assess the result learn ≥75 counted 43 people (79,6%). Because indicator efficacy of research in class action have been reached so that this activity discontinued at cycle 2. Becoming with the usage multimedia in direct instruction model can improve the motivation and result of learning sport nutrition of D2 PGSD Penjas student.